A strategic approach to reducing inter-regional economic differentiation: China’s experience - Yu. V. Vertakova; Ya. Liu (Вестник университета)
This article examines the transition process from a strategy of unbalanced regional development to a strategy of coordinated regional development in China. A number of national strategies and strategic plans for regional development aimed at reducing inter-regional differentiation have been analysed. The paper aims to provide a comprehensive case study of China’s experience in implementing strategic planning to reduce inter-regional economic differentiation. Using the methodology of systems and strategic analysis, the authors analysed the main directions of national strategic regional planning to reduce inter-regional economic differentiation in China. The advantages and disadvantages of approaches to reducing inter-regional economic differentiation have been identified and recommendations for their improvement have been developed. National strategic planning for regional development is an important tool of regional policy to reduce inter-regional economic differentiation. It is necessary to concentrate efforts on ensuring consistency between the central government and local authorities, coordinating different areas of planning and their consistency, and developing a market mechanism.